Voclosporin: a potentially promising therapeutic agent for noninfectious uveitis. (June 2011) - Sepah, Yasir Jamal; Michelle, Elizabeth Harlan; Metcalf, Brandon; Khwaja, Afsheen; Channa, Roomasa; Ibrahim, Mohamed; Hatef, Elham; Heo, Jangwon; Hee, Jeong Lee; Rentiya, Zubir Samsuddin; Do, Diana V; Nguyen, Quan Dong
Voclosporin is a novel calcineurin inhibitor that functions by binding cyclophilin, consequently inhibiting calcineurin activity and preventing the transcription of many genes involved in lymphocyte proliferation and cytokine release. Voclosporin has been shown to be effective in a variety of autoimmune diseases, such as rheumatoid arthritis, psoriasis and renal transplant rejection. Noninfectious uveitis is also an immune-mediated disease which, if left untreated, can cause severe loss of vision. Presently, corticosteroids are the mainstay of therapy in noninfectious uveitis. However, there are several metabolic and ophthalmic adverse effects associated with the long-term use of corticosteroids. Voclosporin has recently been shown in the LX-211 Uveitis Multicenter Investigation of a New Approach to Treatment (LUMINATE) clinical trial program to be effective in the treatment of noninfectious uveitis. With an acceptable side-effects profile, voclosporin is an exciting addition to the therapeutic options available in the management of noninfectious uveitis.